A review of the crinoid columnals (Echinodermata-Crinoidea) from the Carboniferous of Mexico - Buitrón Sánchez, B. E. (2008)
The fossil crinoids and associated fauna from the Carboniferous (Mississippian–Pennsylvanian) of Mexico (Sonora, Tamaulipas, Hidalgo, Puebla, Guerrero, Oaxaca and Chiapas States) are described. Data are based on a combination of field and published sources, including seven previously studied localities from the central and southern areas, and four new localities from the northwestern part of the country. A total of 28 morphospecies are reported, seven from the Mississippian and 21 from the Pennsylvanian. Eleven are recorded for the first time in Mexico. These crinoid columnal morphospecies have been reported from the United States of America (Iowa, Illinois, Kentucky, Kansas, Oklahoma, Colorado and Texas), and there are doubtful reports from Poland, and several Eurasian provinces (Western Siberia, Southern Kazakhstan, Pribalkhash and the Czech Republic). Taxa distribution falls within the northwestern Mid-Continent Realm Tropical Climate Zone. The faunal assemblage comprises fusulinids, corals, bryozoans, brachiopods, trilobites, ammonites and conodonts. Fusulinids (e.g. Fusullinella, Triticites, and Parafusulina) have a Tethyan distribution, are also typical of the American Mid-Continental region, and are similar to fauna of the Eurasian-Arctic Province. Corals (Lophophyllidium, Neozaphrentis, Caninia, Caninophyllum, and Lithostrotionella) are present in the Cordilleran province of North America, and in various Eurasiatic provinces. Whereas fenestellid bryozoans (Fenestella) and brachiopods (Neospirifer, Avonia, Wellerella, Composita, and Hustedia) have a cosmopolitan distribution, the ammonite Peritrochia is distributed in the USA, Sicily, Crimea-Urals- central Asia-Timor. Trilobites (Griffithides) and conodonts (Idiognathoides and Neognathodus) are common in Europe, Australia, and Asia. Rev. Biol. Trop. 56 (Suppl. 3): 1-12. Epub 2009 January 05.